Crisis Management Language during COVID-19: A Corpus-Assisted Analysis of Malaysian Prime Minister’s Discourse - Habibah Ismail; Hazleena Baharun; Hishomudin Ahmad; Mohd Ilias M. Shuhud; Mohd Muzhafar Idrus (Universiti Malaysia Pahang Al-Sultan Abdullah Press (UMPSA Press), 2026)
Indexed by MyCite